2022
DOI: 10.1126/science.abn2479
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and neural basis of pleasant touch sensation

Abstract: Pleasant touch provides emotional and psychological support that helps mitigate social isolation and stress. However, the underlying mechanisms remain poorly understood. Using a pleasant touch–conditioned place preference (PT-CPP) test, we show that genetic ablation of spinal excitatory interneurons expressing prokineticin receptor 2 (PROKR2), or its ligand PROK2 in sensory neurons, abolishes PT-CPP without impairing pain and itch behaviors in mice. Mutant mice display profound impairments in stress response a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 73 publications
0
29
0
Order By: Relevance
“…However, the results of some animal studies have shown that the analgesic mechanism of Tuina may be related to the inhibition of the upward conduction of pain by stimulating receptors on the skin ( 33 , 34 ). Recently, some high-quality research showed that the molecular and neural mechanisms by which a pleasant touch similar to the Tuina effect can reduce stress may be related to the PROK2 neuropeptide encoding pathway and transmission to PROKR2 neurons in the spinal cord ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of some animal studies have shown that the analgesic mechanism of Tuina may be related to the inhibition of the upward conduction of pain by stimulating receptors on the skin ( 33 , 34 ). Recently, some high-quality research showed that the molecular and neural mechanisms by which a pleasant touch similar to the Tuina effect can reduce stress may be related to the PROK2 neuropeptide encoding pathway and transmission to PROKR2 neurons in the spinal cord ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…identified a crucial role of the PROK2-PROKR2 signalling within the spinal circuit in pleasant touch sensation (Fig. 1 ), providing the first evidence for the molecular and neural basis of how pleasant touch information is encoded and integrated from the skin to the spinal cord and highlighting the important role of neuropeptides in the processing of somatosensory information 1 (Fig. 1 ).…”
mentioning
confidence: 92%
“…Modified from the highlighted paper. 1 HC stroking, homecage stroking; Pre-c BL, preconditioning baseline; Pref T, preference test. b Main experiments and findings from the highlighted paper.…”
mentioning
confidence: 99%
See 2 more Smart Citations